Tidal Influence On The Physico-Chemical Parameters, Temporal and Spatial Distribution Of Zooplankton in Langat River-Estuarine Area, Malaysia - Krishantha Jayasinghe, R. P. Prabath (2005)
The objectives of present study were to study the water quality, zooplankton distribution and its community structure along a salinity gradient in Langat river estuarine system (20 46'N, 1010 26' E), during low and high tides. Five sampling stations from the coastal area to the upstream were chosen for this study. Station 1 was in the coastal area while Station 5 was at the most upstream, the rest of the Stations (Stations 2,3 and 4) are located in between, passing along the river gradient. Zooplankton and water samples were collected and analyzed monthly for a period of 12 months (January to December 2003). The water quality, nutrients and zooplankton distribution changed according to the stations and tides. The mean salinity ranged from 32.94k1.20 PSU in coastal waters to 27.78k1.21 PSU in upstream station during high tide. During low tide, the mean salinity in the most upstream station was as low as 1.00k0.90 PSU. Higher Dissolved Oxygen values ranged (means of 5.84k0.35 to 7.09k0.13 mgL-1) during high tide and it decreased (means of 3.91k0.71 to 5.22k0.71 mgL-1) during low tide. On the other hand, the nutrients such as total ammonia nitrogen (ranged from 0.0014k0.001 mgL-1 to 2.5714k0.980 mgL-I), nitrite+nitrate-nitrogen (ranged from 0.0021k0.001 mgL-1 to 0.8100k0.211 mgL-1) and total phosphorus (ranged from 0.0712k0.024 mgL-1 to O.867Ok 0.3241 mgL-l) showed increasing trend from the coastal areas to the upstream. The highest chlorophyll a was recorded at Station 3 with mean values of 10.27k0.84 pgL-I and 3.94k1.06 pgL-1 during high and low tide, respectively. The mean zooplankton density was lowest in the coastal areas (16.21 x 103 k4679.07 individuals m-3) and highest in Station 4 with a mean value 119.81 x 103k43338.73 individuals m-3 during high tide. Copepods dominated zooplankton populations contributing >80% in all the stations throughout the sampling period. The other zooplankton groups such as cnidarians, appendicularians, polychaetes, ostracods, chaetognaths and shrimp larva were distributed in coastal estuarine areas whereas echinoderm larvae were restricted to coastal waters and cladocerans were found only at the upstream stations (Stations 3-5).This study recorded 50 species of copepods which was dominated by the calanoids, Acartia spinicauda, A. amboinensis and A. erythraea accounting for 28%, 18% and 11% of the total copepod populations, respectively. High species diversity occurred in Station 1 decreasing towards the upstream. Species diversity varied depending on the tides, being higher during high tides and than low tides. Some copepod species were highly restricted to the high salinity levels (>30 PSU) while some species could tolerate wide range of salinity from 5 - >30 PSU. Major stenohaline species was Oithona simplex and major euryhaline species were Acartia spinicauda, A. amboinensis and A. erythraea. Zooplankton biomass study showed the highest in station 3 (dry weight 6l2.3Of 26.31 mg m-3 high tide) and lowest in Station 2 (150.051t 54.71 mg m-3 during low tide). This study showed that water quality, nutrient concentrations and the distribution of zooplankton varied according to tides, where high tides resulted in better water quality, higher zooplankton density and higher species diversity compared to low tides. On the other hand, water quality was better and species diversity higher in coastal areas compared to other stations throughout the sampling period regardless of tides.